Pemberian Perlindungan Hukum terhadap Pemegang Polis Asuransi dalam Peraturan Perundang-undangan di Indonesia - Nurrahayu, Feby Dian (Civiliza Publishing, 2024)
Insurance has become a popular investment vehicle due to its offering of certainty and assurance. One common issue faced by policyholders is the difficulty in receiving intermittent reimbursements for specific payments, whereas the primary objective of a policyholder or any party involved in an insurance agreement is to receive compensation when the insured object experiences an unexpected event. Normative legal research methodology is employed as an approach in composing this writing, relying on legal materials obtained through literature research, which includes primary and secondary legal materials. Primary legal sources refer to statutory regulations relevant to the discussion material, while secondary legal sources involve various legal literature and other law-related sources such as legal dictionaries. It can be concluded that legally, an individual possessing an insurance policy holds the position of the insured party entitled to receive premium payments. This is aimed at providing compensation for losses, damages, or potential profit losses that may occur due to an unpredictable event. Individuals holding important roles as insurance policyholders, undoubtedly bound to the insurance company through their insurance agreement, are entitled to legal protection in various legal matters, particularly considering that the majority of insurance policy shareholders are individuals with vulnerable economic conditions. Therefore, several regulations are designed to provide more intensive attention and legal protection to insurance policyholders, preventing potential legal violations that may occur from insurance company entities. This concise abstract falls within the range of 150-200 words and is crafted in academic English.